2006
DOI: 10.1038/442525a
|View full text |Cite
|
Sign up to set email alerts
|

Bees associate warmth with floral colour

Abstract: Floral colour signals are used by pollinators as predictors of nutritional rewards, such as nectar. But as insect pollinators often need to invest energy to maintain their body temperature above the ambient temperature, floral heat might also be perceived as a reward. Here we show that bumblebees (Bombus terrestris) prefer to visit warmer flowers and that they can learn to use colour to predict floral temperature before landing. In what could be a widespread floral adaptation, plants may modulate their tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 8 publications
3
164
1
4
Order By: Relevance
“…This possibility has also been proposed for glossy buttercups (van der Kooi et al ., 2017), which have previously been shown to be warmer at the centre of the flower (Cooley, 1995). Synergy between the attraction of pollinators and the warming of the flower might also be possible, as previous studies have shown that bumblebees prefer warmer flowers (Dyer et al ., 2006). However, our measurements indicate that the centre of the E. californica flower is not warmer than the tips of the petals, and may even be cooler, ruling out a role in intrafloral warming for this particular petal epidermal geometry.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has also been proposed for glossy buttercups (van der Kooi et al ., 2017), which have previously been shown to be warmer at the centre of the flower (Cooley, 1995). Synergy between the attraction of pollinators and the warming of the flower might also be possible, as previous studies have shown that bumblebees prefer warmer flowers (Dyer et al ., 2006). However, our measurements indicate that the centre of the E. californica flower is not warmer than the tips of the petals, and may even be cooler, ruling out a role in intrafloral warming for this particular petal epidermal geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Bombus terrestris is known to discriminate between flowers differing in temperature, scent composition, and nectar sugar concentration and composition (Dyer et al 2006, Whitney et al 2008, Suchet et al 2011. Captive and wild bumble bees in our study thus could have relied for yeast detection on some cue correlated with presence of yeasts in nectar, such as increased temperature, volatile emissions, yeast metabolites (e.g., ethanol), taste alterations, or sugar and amino acids profiles , Canto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dyer et al [11] demonstrated that bumblebees prefer to forage in warmer flowers, which could indicate that food temperature might serve as an additional reward along with the nutrition obtained from nectar. If heat is perceived as a reward, crop loads may increase accordingly; and an increase in crop load of honeybees associated with an increase in air (and presumably nectar) temperature has been demonstrated by Afik & Shafir [12].…”
Section: Introductionmentioning
confidence: 99%